The influence of ongoing task absorption on preschoolers' prospective memory with peripheral cues. Issue 5 (18th August 2019) - Zhang, Xinyuan; Zuber, Sascha; Zhang, Jinrui; Ihle, Andreas; Kliegel, Matthias; Wang, Lijuan
ABSTRACT: Prospective memory (PM) represents the ability to perform a planned action after a certain delay. Substantial increases of PM have been shown across the ages of preschool children. However, previous studies have mostly focused on PM tasks, in which the PM cue was presented centrally (i.e. inside the centre of attention). The current study examined developmental differences between 3-, 4-, and 5-year old preschoolers using PM tasks, in which the PM cue was presented peripherally and investigated the influence of ongoing task absorption on children's performance on such tasks. Results showed that PM performance increased over preschool age and that it was affected by ongoing task absorption, with significantly better PM performance on a low- versus a high-absorbing ongoing task. Importantly, age differences were only present in the low- but not in the high-absorbing condition, showing that preschoolers' PM improves when less cognitive resources are absorbed by the ongoing task.